Le dialecte dans l’œuvre de Felix Mitterer - Delphine Choffat; Elisabeth Kargl (Recherches Germaniques)
In this paper we analyse the use of dialect in two plays as well as a script for a TV film by Felix Mitterer and the challenges this poses for a potential French rendition. To do so, we rely on the translation of In der Löwengrube/Dans la fosse aux lions by Heinz Schwarzinger, alias Henri Christophe, as well as on the subtitling of the TV film Sommernachtsmord made by students of the APC and MCCI master programmes from the University of Nantes. We were able to show that in the case of Kein Platz für Idioten, a play with a universal resonance and written almost entirely in Tyrolean dialect, a transposition into a specific dialect is not necessary. The situation is different for the play In der Löwengrube, where it is absolutely necessary to maintain the coexistence of the different linguistic strata. The task for the translator is then to choose his or her strategies for rendering such a multilayered text in another language, while avoiding the pitfall of an exoticizing translation. In the case of subtitles, the technical constraints and the written medium result in a certain flatness, which is compensated for by the intersemiotic dimension of audio-visual translation.